2010
DOI: 10.1007/s00586-010-1290-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher risk of dural tears and recurrent herniation with lumbar micro-endoscopic discectomy

Abstract: Existing studies on micro-endoscopic lumbar discectomy report similar outcomes to those of open and microdiscectomy and conflicting results on complications. We designed a randomised controlled trial to investigate the hypothesis of different outcomes and complications obtainable with the three techniques. 240 patients aged 18-65 years affected by posterior lumbar disc herniation and symptoms lasting over 6 weeks of conservative management were randomised to micro-endoscopic (group 1), micro (group 2) or open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(189 citation statements)
references
References 22 publications
6
180
1
2
Order By: Relevance
“…The surgical method used in this study, microdiscectomy, seems to be the preferred method in many publications [13][14][15][16][17], and has fewer complications than other methods [18]. This study shows that 75% of the patients with limb paresis due to herniated lumbar disc had full recovery 12 months after micro discectomy.…”
Section: Discussionmentioning
confidence: 65%
“…The surgical method used in this study, microdiscectomy, seems to be the preferred method in many publications [13][14][15][16][17], and has fewer complications than other methods [18]. This study shows that 75% of the patients with limb paresis due to herniated lumbar disc had full recovery 12 months after micro discectomy.…”
Section: Discussionmentioning
confidence: 65%
“…2,3,9,[17][18][19]21,25,26,28,33,36,[41][42][43]45,49,[52][53][54][56][57][58]61 MED techniques employ a longitudinal paramedian incision through which a tubular retractor is placed and visualization is achieved through an endoscope. 2,6,10,13,19,24,25,29,36,46,51,53,57,60,62,64 Percutaneous discectomy entails placing a sheath directly into the disc space via a transforaminal approach, extraforaminal approach, or interlaminar approach and then using a suction/debrider or chemical injection to remove the disc. 1,11,12,23,30,37,44,50 To assess the risk of bias for each study, 3 reviewers (M.F.S., J.J.X., and E.Y.T.)…”
Section: Data Collectionmentioning
confidence: 99%
“…17 In contrast, in a randomized controlled trial, Teli et al demonstrated no difference in overall complications in the tubular microdiscectomy group but did demonstrate increased CSF leaks. 29 Of note, no CSF leaks in the tubular group required operative revision, probably due to the largely intact paraspinal musculature, which eliminates potential space for CSF fistulas to persist. Interestingly, there were no infections in the tubular group, compared with 4%-5% in the standard group.…”
Section: Operative Considerations and Complications Of Tubular Discecmentioning
confidence: 88%
“…17,25,29 In contrast, the trial conducted by Ryang et al demonstrated no difference in operating times. 26 Multiple retrospective studies and a meta-analysis support similar operating times for the tubular and standard groups.…”
Section: Operative Considerations and Complications Of Tubular Discecmentioning
confidence: 90%
See 1 more Smart Citation